Reproductive justice in the face of conservatism: youth attitudes towards abortion on demand (Journal for Studies in Humanities and Social Sciences, 2018)
The right to life and reproductive health has been firmly established by a number of international human rights and gender equality instruments to which Namibia is a signatory. Human rights and reproductive justice frameworks affirm women’s right to bodily integrity and reproductive autonomy without violence, coercion or discrimination on the basis of race, class, ethnicity or disability. The restrictive Namibian abortion law infringes upon all these rights. It is particularly discriminatory against poor and mainly black women who do not have the means to seek safe and legal abortions outside the borders of the country. The high levels of morbidity and mortality related to unsafe illegal abortions show that criminllisation does not stop illegal abortions from taking place. Government has made some attempts at re-viewing the outdated law, but progress has been stymied by politically conservative attitudes and the lack of awareness of gender equality and reproductive rights. Although people (in this case youth) are aware of the risks of unsafe illegal abortions to women’s lives and health, they do not see a need for change. This raises broader questions about the status of women in our society and whether women’s lives matter.